Penerapan Metode Weighted Product Dalam Menentukan Siswa Bermasalah di SMAN 05 Seluma - Purwanto Hidayat Syaputra; Khairullah Khairullah; Pahrizal Pahrizal; AR Wallad Mahfuzi (Jurnal Media Infotama, 2023)
In the current era of globalization, advances in science and technology are developing very rapidly, especially in terms of decision making. The importance of making fast and accurate decisions is increasingly emphasized in the era of globalization due to the increasing uncertainty and complexity of problems. Therefore, a system that can assist in decision making is very important. In the school environment, the presence of problem students can be one of the factors that affect comfort in the teaching and learning process. Students who often make problems at school can disrupt the teaching and learning process in class. Therefore, teachers and school administrators, especially BK teachers, must immediately address this problem by providing guidance and direction to problem students. Because of the importance of identifying students with problems quickly and precisely, it is necessary to have an effective and accurate determination. However, currently at SMAN 05 Seluma, the process of determining problematic students still uses the manual method by using paper as a tool for data storage and processing. The weighted product (WP) method was chosen because it can provide results that are more accurate and easy to understand. In this method, each factor has a different weight depending on how it relates to student problems. A decision support system application has been produced that can perform calculations using the weighted product method in determining problem students. The application is WEB-based using the programming language PHP and MYSQL as the database.